Servicing Map Users at Aalborg University Library - Stevenson, Bill (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2000)
This is intended as a short discourse to explain the current policies for the development and management of the Map Collection, and for the provision of services, at Aalborg University Library, Denmark.